Smith Predictor-based Control of Systems with Time Delay - Iampita, Ivan Manuel (Universiti Teknologi PETRONAS, 2017)
Smith Predictor is an effective method for control of processes in which the process time delay is long as it improves the performance of a PI controller. However, processes are susceptible to delay variation due to uncertainties and this predictive model does not guarantee plant robustness and stability due to the increase of negative phase lag. A temperature control experiment is conducted in a shell-tube Heat Exchanger Process Pilot Plant due to its time delay presence characteristic of interest. The process model in the form of transfer function is identified using Statistical Modelling with accuracy of 93.86%. A Smith Predictor-PI controller is developed using Matlab/Simulink to simulate the control of the temperature loop and results using performance indicators such as Integral Absolute Error (IAE) and Integral Square Error (ISE) show that it performs better than a PI controller.